“Apenas um jovem leitor”: discursos sobre a leitura numa página do Facebook - Carvalho, Elisângela Santos de (2014)
The Information and Communication Technologies (ICT) have promoted and encouraged several changes in various scopes of social life. One of the areas in which we can observe these changes with greater intensity is cyberspace, especially social networks. Currently, Facebook has become one of the most popular social networks in the world, and therefore a useful place to study today’s reading and writing practices. This study aimed to analyze the discourses about the reading and writing practices on a Facebook fan page called Apenas um Jovem Leitor, which at the completion of the survey had about 2,850 "likes" and 9 "top fans", who participated by posting on this page. The analysis was made from verbal and nonverbal extracts from the page, and it showed that reading brings out a teenager enunciator, constructing meanings about reading that, in most cases, differ from those constructed by the discourses that the school officially puts into circulation through several prescribed pedagogical practices. We tried to see what these youngsters comment and write in this space about their reading preferences. What do they say about them and what kind of reading do they suggest to their peers? For this study, we reflected on the shift in reading and writing practices from a hard copy culture to a screen culture or cyberculture, grounded on the proposals of Roger Chartier, Lévy, Bauman, Lemos and Recuero. For the composition and analysis of the corpus we used the theoretical and methodological contributions of the french Discourse Analysis, especially the concepts of ethos and scenography as proposed by Dominique Maingueneau. The analysis shows that young people read and write a lot today, however, what they read is not always the classics from the canonical literature valued in school. Keywords: Discourses about reading; Facebook; ethos; scenography.